Functional outcome of non-vascularized fibula in gap non union - Yadav, Amit Kumar; Pawar, Eknath; G. S., Prasanna Kumar; Mane, Akash; Harssor, Abhishek; Shet, Vipul; Bansal, Sagar (International Journal of Research in Orthopaedics, 2019)
Background: Gap non-union is one of the most perplexing problems facing the orthopedic surgeon today. Fibula is the preferred site of non-vascularized bone graft due to its easy accessibility to surgical resection and minimal donor site complications. Methods: The study comprised 11 patients of gap non-union between 13 to 80 years (mean=34.9 years). The fibular graft was harvested from the mid shaft and cortico-cancellous bone graft taken from the iliac crest was applied at both ends of the fibular graft to aid in union. Results: The average bone gap was 7 cm (4-13 cm). 64% of the patients achieved bone union after the first procedure, of the remaining 4 patients, 1 patient showed union after secondary cortico-cancellous bone grafting, while two are planned for the same. The remaining one patient has only completed 16 weeks follow-up at present and is not showing signs of union at present. Functional range of motion was achieved in both the proximal and distal joints in all cases. Conclusions: Non-vascularized fibular bone grafting is a simple and effective treatment option which does not require any special skill, has a very low complication rate and has very high patient compliance.